Does prophylactic inferior vena cava filter reduce the hazard of pulmonary embolism and mortality in severe trauma? A single center retrospective comparative study. (2021) - Tran, Thien Trung; Bjarnason, Haraldur; McDonald, Jennifer; Goss, Brian; Kim, Brian; Houghton, Damon E.; Stavem, Knut; Kløw, Nils Einar
Highlights: Severely injured trauma patients are at high risk of venous thromboembolism. Use of IVC filters in trauma patients without recent history of venous thromboembolism is controversial. IVC filter placement did not reduce the hazard of pulmonary embolism or mortality but may pose an increased hazard of deep venous thrombosis. Abstract: Objectives: Use of inferior vena cava (IVC) filters in patients following severe trauma without recent history of venous thromboembolism (VTE) is controversial. Our objective was to determine if IVC filter placement in the setting of severe trauma effects the hazard of in-hospital pulmonary embolism (PE), deep venous thrombosis (DVT) and mortality. Methods: This retrospective study recruited patients from a single Level I Trauma Center between 1/2008 and 12/2013. Inclusion criteria were age>15 years, Injury Severity Score (ISS)>15 and survival>24 h after hospital admission. Patients with VTE diagnosed prior to IVC filter placement were excluded. A Cox proportional hazards regression model was used, adjusting for immortal time bias with landmark analysis at predefined time after injury. Differences between IVC filter and non-IVC filter groups were adjusted using propensity score. Results: In total 1451 patients were reviewed; 282 patients received an IVC filter and 1169 patients had no IVC filter placed. The mean age was 45.9 vs. 56.9 years and the mean ISS was 29.8 vs. 22.6 in the IVC filter and the non-IVC filter group, respectively. IVC filter placement was not associated with the hazard of PE (HR = 0.46; 95 % CI, 0.12, 1.70; P = 0.24) or mortality (HR = 1.02; 95 % CI 0.60, 1.75; P = 0.93). However, IVC filter placement was associated with the hazard of DVT (HR = 2.73; 95 % CI, 1.28, 5.85; P = 0.01). Conclusions: In patients with severe trauma, those with prophylactic IVC filter placement did not have a reduced hazard of PE or mortality, but an increased hazard of DVT was observed.